Effects of Biofertilizer, Cowpat Ash and Phosphorus on Seed Yield of Alfalfa - Dasci, Mahmut; omakli, Binali (Asian Journal of Chemistry, 2010)
The aim of this study was to evaluate the effects of biofertilizer (Bacillus megatherium var phosphaticum), cowpat ash and phosphorus fertilization on seed yield and seed weight of alfalfa. The increasing rate phosphorus fertilizer affected seed yield and seed weight of alfalfa. The highest seed yield and seed weight obtained from the application of 150 kg ha-1 P2O5, the lowest was in without P2O5 plots. The bacterium treatment significantly increased seed yield. Seed yield and 1000 seed weight were 346 kg ha-1 and 1.82 g in without bacterium plots, respectively. In bacterium treated plots seed yield was 367 kg ha-1, 1000 seed weight was 1.84 g. Application of cowpat ash increased seed yield and seed weight but the increasing is not significant.